2009
DOI: 10.1093/rpd/ncp126
|View full text |Cite
|
Sign up to set email alerts
|

AVIDOS--a software package for European accredited aviation dosimetry

Abstract: AVIDOS is a computer code used for the dose assessment of aircraft crew exposed to cosmic radiation. The code employs a multiparameter model built upon simulations of cosmic radiation exposure done using the FLUKA Monte Carlo code. AVIDOS calculates both ambient dose equivalent H*(10) and effective dose E for flight routes over the whole world at typically used altitudes and for the full range of solar activity. The dose assessment procedure using AVIDOS is accredited by the Austrian office for accreditation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…It is should be emphasized that the missions were dedicated to this study with rigorous monitoring, which allowed a rigorous evaluation in this geographic region that is subject to the possible effects of the SAA. The experimental results, when compared to the estimates obtained using the computer code CARI-6 [11], EPCARD [11], EXPACS [22,23] for the dose rate in estimative FP missions and the codes AVIDOS [24], CARI6 and PCAIRE [25] for accumulated dose estimation in the route for RM, show that the computational estimates present a good agreement with the measurements considering the typical and acceptable uncertainties. In measurements at a fixed point at different distances from the SAA center (Fig 10), it was observed that there was no observable systematic effect, confirming that there is not influence of the SAA on the radiation dose at flight altitude, at least in calm solar and magnetospheric conditions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It is should be emphasized that the missions were dedicated to this study with rigorous monitoring, which allowed a rigorous evaluation in this geographic region that is subject to the possible effects of the SAA. The experimental results, when compared to the estimates obtained using the computer code CARI-6 [11], EPCARD [11], EXPACS [22,23] for the dose rate in estimative FP missions and the codes AVIDOS [24], CARI6 and PCAIRE [25] for accumulated dose estimation in the route for RM, show that the computational estimates present a good agreement with the measurements considering the typical and acceptable uncertainties. In measurements at a fixed point at different distances from the SAA center (Fig 10), it was observed that there was no observable systematic effect, confirming that there is not influence of the SAA on the radiation dose at flight altitude, at least in calm solar and magnetospheric conditions.…”
Section: Discussionmentioning
confidence: 77%
“…The codes used were CARI-6 [11], EPCARD [11], EXPACS [22,23] for the dose rate estimative in FP missions, the codes AVIDOS [24], CARI-6 and PCAIRE [25] for the route accumulated dose estimation for RM, and the code QARM [24] for the neutron/non-neutron ratio estimative.…”
Section: Computational Codesmentioning
confidence: 99%
“…The mission of the Solar Weather Expert Service Centre (S-ESC) is to provide and develop the functionalities, capabilities and expertise in the domain of Solar Weather that are needed within the ESA SSA SWE Network to achieve as a collaborative enterprise its mission of demonstrating and assessing the influences of Space Weather and informing and supporting end-users through the provision of accurate, reliable and timely products and (pre) operational services, tailored to their requirements [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Mission Statementmentioning
confidence: 99%
“…Upper panel: GLE alert service provided by the University of Athens [12]. Lower panel: Radiation exposure estimation at aircraft altitude (AVIDOS) provided by Seibersdorf Laboratories [13]. Courtesy of the ESA SWE Portal (http://swe.ssa.esa.int/ space radiation).…”
Section: Expert Groupsmentioning
confidence: 99%
“…Assessment of the radiation exposure, henceforth exposure, at typical flight altitudes is an important topic in the field of space weather (e.g., Baker, ; Latocha et al, ; Lilensten & Bornarel, ; Mertens, ; Mertens et al, , and references therein). Individual accumulated doses of the cockpit and cabin crew are monitored, and crew members are regarded as occupational workers (EURATOM, ; ICRP, ).…”
Section: Introductionmentioning
confidence: 99%